A preliminary assessment of large mammal and bird use of different habitats in Bwindi Impenetrable National Park - Olupot, W.; Sheil, Douglas (2011)
Understanding species distributions, habitat requirements, and population trends is helpful for implementing effective conservation. But expense often prevents such evaluations. Here, we present a preliminary assessment for a low-cost method – road-side observations – to see how effective it can be. The bamboo zone of Bwindi Impenetrable National Park is restricted, covering 0.3% of park area yet is poorly known. Our study evaluates the use of the bamboo zone and surrounding forest by species of large mammals and large ground birds. Data were collected while driving a road section running through this zone. During 416 trips, seven species of mammal and one bird were recorded. Distributions for most species were significantly nonrandom in both space (P < 0.02) and time (Hour of day: P < 0.040; Month: P < 0.0001) for all species but black-fronted duikers and blue monkeys for which 0.085 > P > 0.050 for month. Of the species observed, francolins were more frequently seen in the zone of visible bamboo than the nonbamboo zone (P = 0.002). Black-and-white colobus, L’Hoest’s monkey, and jackals were more common in nonbamboo forest (P = 0.05). Road sightings have potential for low-cost habitat use assessments and monitoring.